Color Laser Marking: Repeatability, Stability and Resistance Against Mechanical, Chemical and Environmental Effects - Hamid Roozbahani; Marjan Alizadeh; Heikki Handroos; Antti Salminen (IEEE, 2022)
In this paper, utilizing the technology of color laser marking of stainless steel in industrial productions is investigated from the perspective of repeatability and stability of produced color markings. The color laser marking has remarkable advantages over conventional metal coloring methods; however, in order to implement this technology in industry, the reliability, stability and quality of resulting markings must be endorsed. For this purpose, an AISI 304 color palette made up of fifteen colors was evolved. The dependence of produced colors on different laser processing parameters were analyzed. Afterward, the produced colors were tested utilizing optical, scanning electron and atomic force microscopy, and the configuration of oxide films was specified through Raman spectroscopy. The obtained colors had proper uniformity, brightness, and cover almost all spectral regions. Also, color standardization and palette repeatability test were performed by assessing and evaluating the reflectance spectra of the formed colors. The color palette demonstrated high repeatability for all colors except for one specific color. Moreover, the stability of color markings in terms of environmental, mechanical and chemical resistance was investigated. The resulting colors showed high resistance in most of the environmental conditions; however, exposure to very high temperatures and extreme humidity ( 100∘C , 90%) and low temperature and extreme humidity ( −40∘C , 90%) leads to deterioration of few colors. Color marks showed high hardness and excellent mechanical stability to external impacts and outstanding resistance to various chemicals, excluding acidic solutions and salts.